Thoracoscopic Pleural Biopsy as an Aid to Diagnosis in Pediatric Tuberculosis with Pleural Involvement - Keys, Charles; McLeod, Elizabeth; Pesti, Christopher; Armstrong, David (European Journal of Pediatric Surgery, 2012)
Introduction Successful treatment of tuberculosis relies on microbiological diagnosis and drug sensitivities. Due to the pauci-bacillary nature of childhood infection, this is often not possible. We describe the successful microbiological diagnosis of tuberculosis using thoracoscopic pleural nodule biopsy.Material and Methods In seven patients presenting with pulmonary tuberculosis and pleural involvement, but in whom microbiological diagnosis could not be established, thoracoscopic pleural biopsy was performed and analyzed for histology, acid-fast bacilli, polymerase chain reaction (PCR), DNA, culture, and drug sensitivities.Results In five out of the seven patients we achieved positive histology, culture, and drug sensitivities. In the remaining two patients, histology, PCR, and DNA probe were positive for tuberculosis.Conclusions Thoracoscopic pleural biopsy is a sensitive aid to the diagnosis of pleural tuberculosis in children.
Keywords: tuberculosis; thoracoscopy; diagnosis; biopsy; children